2014
DOI: 10.5812/ircmj.5186
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Problem-based Learning With Lecture-based Learning

Abstract: Background:Problem-based learning (PBL) is one of the most commonly used educational methods in medical schools of different countries. By working through this method, students think critically, generate ideas, and acquire the knowledge and skills required to become a doctor.Objectives:This study aimed to compare problem-based learning with lecture-based learning in the education of medical students.Materials and Methods:This crossover interventional study was conducted on 40 medical students in pediatric ward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 18 publications
4
44
1
2
Order By: Relevance
“…However a previous study stated that the student performance in a problem oriented pharmacobiochemistry course was significantly better than their performance in a lecture based course [14,1]. Unlike our findings, Khoshnevisasl P and his colleagues in 2014 [15] mentioned that There was no significant difference between students performance in a lecture based exam and a problem based learning sessions exam .…”
Section: Discussioncontrasting
confidence: 92%
“…However a previous study stated that the student performance in a problem oriented pharmacobiochemistry course was significantly better than their performance in a lecture based course [14,1]. Unlike our findings, Khoshnevisasl P and his colleagues in 2014 [15] mentioned that There was no significant difference between students performance in a lecture based exam and a problem based learning sessions exam .…”
Section: Discussioncontrasting
confidence: 92%
“…18 Likewise, another study revealed that integrated curriculum promoted better understanding of health sciences pertaining to common diseases and majority of the respondents (77.61%) expressed that PBL in modules assisted to great extent in interpreting the cases in their annual examinations.…”
Section: Resultsmentioning
confidence: 98%
“…[21214] Moreover, previous studies have also shown that 78% and 52.3% of the students perceived that PBL sessions were interesting[1516] and help in improvement of knowledge, skills, and critical thinking abilities. [171819] Callis et al . reported that students who enrolled in a hybrid PBL curriculum demonstrated a greater ability to apply basic science principles to a clinical scenario when compared to traditional lecture-based students.…”
Section: Discussionmentioning
confidence: 99%